PEMBAHARUAN KURIKULUM PAI DAN MACAM-MACAM BENTUK KURIKULUM - Ru’yatul Lailah (QATHRUNÂ, 2022)
Today, the world of education is faced with the challenges of the times. Progress in varios fields of life such as science., technology, and economics requires education to improve its quality, in order to be able to face the challenges of the times. Changes in socety that are so rapid due to ideological, social, cultural, and economic developments must be quickly responded by the community as agents of change itself through education, one of the respones is renewal in the field of curriculum. The renewal of the Islamic Religious Education Curriculum is a necessity to balance the changes that occur in society and to balance the progress of the times, ut the renewal is stil guided by the Qur’an and Hadith as a source of Islamic education. Curruculum renewal should be carried out the prepare a generation of Muslims who strong in faith, have good morals, have the spirit to do good deeds, are broad and knowlegdeable in their religion, are technologically capable and are able to take advantage of various technological sophistications for the advancement of their religion, nastion and country.